The Karma of Words Buddhism and the Literary Arts in Medieval Japan. - LaFleur, William R. (University of California Press, 1986)
""A masterly book . . . will prove of great assistance to a student of Japanese literature and thought from the eleventh century onwards.""--Times Literary Supplement ""A major contribution to the fields of Japanese studies, comparative literature, and history of religions . . . a book that begs for classroom use.""--The Eastern Buddhist ""Innovative and provocative . . . will be of interest not only to specialists in Japanese religion and Japane.